ANALISIS POLYCHOTOMOUS RASCH MODEL UNTUK KALIBRASI SOAL ANALISIS REAL PADA PROGRAM STUDI TADRIS MATEMATIKA - Jerhi wahyu fernanda; Eka Resti Wulan (EMTEKA: Jurnal Pendidikan Matematika, 2024)
Student scores in real analysis courses are still not optimal with some students still having grades in the lower category. Efforts that can be made is to ensure that the exam questions are appropriate to be used to measure student abilities. Calibration of exam questions is carried out to ensure that the questions used are accurate in predicting participants' abilities. The Polychotomous Rasch Model is the development of the Rasch model which is used for polychotomous cases. Partial Credit Model (PCM) is part of the Polychotomous Rasch Model which is used to analyze polychotomous questions where each question has a different category. This study aims to examine the feasibility of midterm and final semester exam questions for real analysis courses in the form of essay questions using the PCM method in the Mathematics Tadris study program at IAIN Kediri. Research uses the type of research and development. The instrument used is a matter of real analysis ability which is essay in nature and consists of 10 questions. Data collection is done by using total sampling technique. The results of the descriptive statistical analysis showed that the average UTS and UAS scores were 64.53 and 56.42, respectively. The results of the analysis using PCM concluded that the UTS and UAS questions fulfilled validity because they had infit and outfit values in the specified range. The results of the analysis through the wright map provide wrightmap information. Information is obtained for the easiest midterm exam question which is question number 6 and the most difficult is question number 5. In the wrightmap image for UAS questions, the easiest question is question number 1 and the most difficult is question number 5.